THE EFFECTIVENESS OF THE PEACE DECISION IN THE DISPUTE OF CIVIL CASE PERMA NO. 1 OF 2008 IN THE MAKASSAR DISTRICT COURT - Deselfia DNM Sahari (Jurnal Syntax Transformation, 2023)
This study aims to determine the effectiveness of peace decisions in civil case disputes according to PERMA No. 1 of 2008. As well as to find out the legal consequences that arise if a peace agreement in a civil case dispute is violated by one or both parties because of a bad faith. The research was conducted at the Makassar District Court and the Makassar Religious Court. The method used in this study is sociological juridical, namely by studying various legal provisions relating to the effectiveness of peace agreement decisions in civil case disputes according to PERMA No. 1 of 2008 as the latest regulation governing the Mediation process in Court. In the results of the study, it is known that the files of the peace agreement, have not been seen uniformly in the mention of terms. PERMA No. 1 of 2008 has provided a more comprehensive, more detailed arrangement with respect to the mcdiation process in court. It is also possible for mediation to be pursued at the level of appeal or cassation. This PERMA also has shortcomings such as conflicting articles. Article 2 (paragraph 1) states that PERMA only applies to cases that are processed in court, while Article 23 (paragraph 1) states that it is permissible to bring the results of a peace agreement passed outside the court to obtain a peace deed. Even though this authority has not become the authority of the court.